Makna Istilah Sebutan Untuk Tuhan “YHWH“ Sesembahan Umat Beriman di Kitab Perjanjian Lama - Andreas Danang Rusmiyanto (Sekolah Tinggi Teologi Borneo, 2022)
Abstract: The name of Allah is an issue that often intersects with dogma. In the religion understoodor known as YHWH, Addonay is translated as god. For that name is very sacred to all who are called.But God wanted his creation to know him so he introduced his name to his people in various ways,mentioning the essence of the name. The purpose of this scientific work is to describe one of thenames of God, especially the book of Exodus 6:2 and the use of the expression in several books of theOld Testament. The research methodology of this scientific article uses qualitative methods byanalyzing the meanings of terms and words. Given the majesty of Allah's name, any use of Allah'sname that insults Him and His attributes is an attack on Allah's name. The third commandment of theTen Commandments forbids taking God's name in vain as it shows a lack of respect for God Himself.According to God in His statement, anyone who abuses God's name is